v.19 - "Keynes, John Maynard" (New Delhi, 2013)
This volume brings together Keynes's attempts to influence public opinion and policy concerning primarily British affairs between 1922 and 1929. During this period, his major concerns were Britain's attempt to return to the gold standard and its consequences, industrial policy (especially in the cotton textile industry) and unemployment policy, although he became briefly involved in many other subjects. Most of the volume consists of Keynes's journalism for the period, but it also contains his previously unpublished evidence to official committees, anonymous contributions to The Nation and Athenaeum and related correspondence.
Keywords: Keynesianism